A batch scheduling model for a three-stage flow shop with job and batch processors considering a sampling inspection to minimize expected total actual flow time - Pratya Poeri Suryadhini; Sukoyo Sukoyo; Suprayogi Suprayogi; Abdul Hakim Halim (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: This research develops a batch scheduling model for a three-stage flow shop with job processors in the first and second stages and a batch processor in the third stage. The model integrates production process activities and a product inspection activity to minimize the expected total actual flow time. Design/methodology/approach: The problem of batch scheduling for a three-stage flow shop is formulated as a mathematical model, and a heuristic algorithm is proposed to solve the problem. This model applies backward scheduling to accommodate the objective of minimizing the expected total actual flow time. Findings: This research has proposed a batch scheduling model for a three-stage flow shop with job and batch processors to produce multiple items and an algorithm to solve the model. The objective is to minimize total actual time. The resulting production batches can be sequenced between all types of products to minimize idle time, and the batch processor capacity affects the sample size and indirectly affects the production batch size. Originality/value: This research develops a batch scheduling model for a three-stage flow shop constituting job and batch processors and carrying out integrated production and inspection activities to minimize the expected total actual flow time.
Keywords: 650; Actual flowtime; batch scheduling; a three-stage flow shop; job processor; batch processor; sampling inspection